2021
DOI: 10.1002/cjoc.202100145
|View full text |Cite
|
Sign up to set email alerts
|

Decavanadate‐based Transition Metal Hybrids as Bifunctional Catalysts for Sulfide Oxidation and C—C Bond Construction

Abstract: Main observation and conclusion The development of bifunctional catalysts has drawn much attention in realizing efficient and feasible catalytic systems to meet the diverse demand of potential industrial applications. Design of stable and powerful bifunctional catalysts for various catalysis systems is highly desirable yet largely unmet. Here, three kinds of decavanadate‐based transition metal hybrids (DTMH) (i.e., Co‐DTMH, Ni‐DTMH and Ag‐DTMH) have been successfully synthesized through a pH tuning strategy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 57 publications
1
15
0
Order By: Relevance
“…[57] For instance, transition metal-decorated imidazole derivatives stabilized decavanadate clusters and resulted in the formation of bifunctional catalysts. Among them, [44] The combination of transition metal ions with POM polyoxoanions or heteropoly acids can endow them with both Lewis acid-base or Lewis-Brønsted acidic sites. Tian and coworkers reported the synthesis of [Zn(bix)]{V 2 O 6 } (bix = 1,4bis(imidazole-1-ylmethyl)benzene) as a bifunctional Lewis acidbase catalyst for CÀ C bond formation through Knoevenagel and cyanosilylation reaction in solvent-free conditions.…”
Section: Synthesis Of Bi/multifunctional Pom-based Hybridsmentioning
confidence: 99%
See 1 more Smart Citation
“…[57] For instance, transition metal-decorated imidazole derivatives stabilized decavanadate clusters and resulted in the formation of bifunctional catalysts. Among them, [44] The combination of transition metal ions with POM polyoxoanions or heteropoly acids can endow them with both Lewis acid-base or Lewis-Brønsted acidic sites. Tian and coworkers reported the synthesis of [Zn(bix)]{V 2 O 6 } (bix = 1,4bis(imidazole-1-ylmethyl)benzene) as a bifunctional Lewis acidbase catalyst for CÀ C bond formation through Knoevenagel and cyanosilylation reaction in solvent-free conditions.…”
Section: Synthesis Of Bi/multifunctional Pom-based Hybridsmentioning
confidence: 99%
“…For example, in the presence of Co(OAc) 2 and isopropyl imidazole (1‐ip‐IM), single crystals of [Co(1‐ip‐IM)(H 2 O) 5 ] 2 (H 2 V 10 O 28 ).6H 2 O were isolated while replacing Co(OAc) 2 with AgNO 3 resulted in a powder product. Hence, 1‐Et‐IM was used to react with AgNO 3 and afforded the single crystals of [Ag(1‐Et‐IM) 2 ] 2 [Ag 2 (1‐Et‐IM) 4 ] 2 [H 3 V 10 O 28 ] 2 .2(1‐Et‐IM).2H 2 O [44] …”
Section: Pom‐based Inorganic‐organic Hybridsmentioning
confidence: 99%
“…Polyoxometalates (POMs) are a class of negatively charged metal oxide clusters with tailorable crystalline structures, which consist of high-valence early transition metals and have great potential for applications in the fields of electrochemistry, 1 catalysis, 2 sensing detection, 3 photochemistry, 4 energy chemistry, 5 etc . Nevertheless, the facile dissolution and difficulty of separating the POMs in a homogeneous system to increase the accessible space for the catalytic reaction are fatal drawbacks in various POM-catalysed organic reactions, such as esterification, 6 olefin epoxidation, 7 alcohol oxidation, 8 etc .…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazoles are important compounds in the fields of pharmaceutical chemistry, agricultural chemistry, and synthetic organic chemistry. The direct condensation of hydrazines with 1,3-diketones is a more efficient method to successfully obtain pyrazole derivatives; it represents the most straightforward and effective method owing to significantly high overall reaction efficiencies and improved atom economy . Traditionally, Lewis acids or Brønsted acids are applied as catalysts for this transformation, such as Sc­(OTf) 3 , sulfuric acid, and so on. Recently, it was reported that the Lewis acid-base catalytic system would be beneficial for this reaction. , However, there are very rare examples of the condensation reaction of hydrazines with 1,3-diketones catalyzed by the bifunctional Lewis acid-base catalyst up to now. The development of efficient bifunctional catalysts for the construction of pyrazoles still is a significant work in current research.…”
Section: Introductionmentioning
confidence: 99%